Surgical Outcomes after Bucket Handle Meniscus Repairs: analysis of a large contained cohort study. Issue 7 (30th July 2021) - Tucker, Lue-Yen; Vieira, Amy; Ding, David
Objectives: Comprising approximately 10% of all mensiscus tears, bucket-handle meniscus tears are large longitudinal vertical meniscus tears that have an attached fragment flipped into the intercondylar notch. Meniscectomy would often result in significant meniscal loss and increased joint loading. Alternatively, meniscus repair attempts to restore the function of the meniscus and aims to preserve joint mechanics. The objective of this observational data-only study is to evaluate the long-term risk of subsequent ipsilateral knee surgery in patients who underwent a bucket handle meniscus repair and assess risk factors associated with subsequent knee surgical intervention. Methods: We performed an electronic health records search for all patients who underwent arthroscopic knee meniscal repairs from 2011 to 2018. Natural language processing was used to search for terms of interest in the long operative notes to determine if these surgeries were performed for bucket handle meniscus tears. These patients comprised our initial cohort. Study subjects were followed for at least one year and up to five years with censoring at death, membership disenrollment, or 12/31/2019. Baseline patient characteristics and outcomes (i.e., subsequent operative procedures, deep surgical site infections, and deep venous thrombosis) were evaluated via a database review. Descriptive statistics were employed. Results: The median follow-up time was 4.2 years (interquartile range [IQR] 2.7-5.0 years). A total of 1353 patients underwent meniscus repair surgery for a bucket-handle meniscus tear. The median age was 24 years (IQR 17-34). During the follow-up period, 492 subsequent ipsilateral procedures were performed in 272 (20.1%) patients. 59 (4.3%) patients underwent a subsequent repeat meniscus repair and 164 (12.1%) patients underwent a subsequent meniscectomy. The median time to first procedure was 41.1 months (IQR 23.3-60 months). Younger age and lower BMI were significant risk factors for having subsequent surgery (adjusted odds ratio [aOR] 1.04, 95% Confidence Interval [95%CI] 1.02-1.05, and aOR 1.60, 95%CI 1.09-2.35, respectively). Patients undergoing concomitant ACL reconstruction had a lower risk of undergoing subsequent surgery (aOR 0.66, 95%CI 0.50-0.88). Conclusions: This is the largest reported contained patient cohort study on outcomes after bucket-handle meniscus repair. 20% of patients underwent repeat surgery during the follow-up time period with 4.3% experiencing a subsequent repeat meniscus repair and 12% experiencing a subsequent meniscectomy. Risk factors for subsequent surgery include younger age and lower BMI. Concomitant ACL reconstruction at time of bucket-handle meniscus repair reduced the risk of subsequent reoperation. :